2017
DOI: 10.1002/pmic.201600373
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Extracellular Matrix Proteome Reveals Discrete Mechanism Regulating Verticillium Dahliae Triggered Vascular Wilt Disease in Potato

Abstract: Plants exposed to patho-stress mostly succumb due to disease by disruption of cellular integrity and changes in the composition of the extracellular matrix (ECM). Vascular wilt, caused by the soil borne hemibiotrophic filamentous fungus Verticillium dahliae, is one of the most significant diseases that adversely affect plant growth and productivity. The virulence of the pathogen associated with the ECM-related susceptibility of the host plant is far from being understood. To better understand ECM-associated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Regarding biotic stresses, some reports identified DUF538 transcripts or proteins in response to infection by fungal pathogens [13][14][15][16], where they seem to be important activators of the plant antioxidative system and a common component in the responses of different stress-challenged plants [17][18][19]. Additionally, a study of grapevine (Vitis vinifera) showed that genes encoding sugar transporters containing a DUF538 domain, such as SWEET17 proteins, are significantly upregulated in leaves infected with phytoplasma [20].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding biotic stresses, some reports identified DUF538 transcripts or proteins in response to infection by fungal pathogens [13][14][15][16], where they seem to be important activators of the plant antioxidative system and a common component in the responses of different stress-challenged plants [17][18][19]. Additionally, a study of grapevine (Vitis vinifera) showed that genes encoding sugar transporters containing a DUF538 domain, such as SWEET17 proteins, are significantly upregulated in leaves infected with phytoplasma [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, unraveling the repertoire of extracellular matrix proteins for managing rot fungus would offer insight into key processes that regulate disease or immune response. Various studies to date reported the ECM proteome of plants in response to hemibiotrophic fungal pathogens, particularly Fusarium and Verticillium , and highlighted the role of ECM proteins in disease and defense pathways. Also, Fusarium verticillioides elicitor-induced changes were reported in the maize extracellular matrix proteome . In this study, we investigated the stem rot responsive temporal ECM proteome using (isobaric tags for relative and absolute quantitation) iTRAQ based quantitative proteomics to understand wall mediated changes triggering disease responses in a jute variety in response to M. phaseolina attack.…”
Section: Introductionmentioning
confidence: 99%